Study of Ecotourism Sustainable Development Strategy of the Cinsibu Atayal Tribe in Taiwan - Chang, Hsiao-Ming; Lin, Chi-Jen; Hung, Chien-Jen (IOP conference series. Earth and environmental science, 2020)
This study aims to analyze the processes and measures of the sustainable tourism development of indigenous tribes, and explores the policies of governmental departments, in order to serve as reference for the development of tribal tourism. This study treats the Cinsibu Atayal Tribe in Taiwan as the subject and conducts qualitative research. According to the findings: (1) Policy guidance of the government and clergymen in the tribe are the main forces to promote sustainable tribal ecotourism development. (2) Tribal ecotourism can effectively carry out ecological conservation and maintain and pass on culture. (3) By the creation of job opportunities in the tribe, the people can be self-sufficient, which results in sustainable development in the tribe. According to the results, this study proposes suggestions for the development of tribal ecotourism.